The clinico-pathological findings of surgically treated goiter - Al Ali, Thamer T.; Mattar, Ayad Jassim; Al-Majedy, Ali Kareem (AL-Kindy College Medical Journal, 2015)
Background: Goiter is one of the most common conditions that affect people’s at different age groups with its effect on the metabolic status of the body through the hyper&/hypo functioning gland that may needs surgical resection. This prospective study had been conducted on 100 patient (85 females&15 males} at the specialized center for endocrinology and diabetes mellitus in Baghdad city, between Jan.2013-Oct.2014;Their ages were ranging between 11-75 years ; the median age is (40.5 years) .Objectives: define the clinic-pathological pattern of goiter in the center .Methods: This is a prospective study at the specialized center for endocrinology & diabetes in Baghdad at ALRissafa district; including 100 patients (84 females&16 males). They have their thyroid operation at Al-Kindy teaching hospital and AL-Jadirya privet hospital during the period extending between January 2013 to October 2014. The histopathological results were grouped into Colloid nodular goiter ,thyroid adenoma , thyroiditis ,toxic nodular goiter ;diffuse toxic goiter and thyroid malignancy.Results:Goiter affect females (85%) more than males (15%) with ratio of 5.6/ 1 & the most affected age group is those between 30-49 years68%. The most common presenting symptom was mass in the neck (45%).The most common pathology of goiter was colloid nodular goiter (69%) the most common malignant lesion was papillary carcinoma(4%)& follicular (1%).(7%) of goiterous patients were affected by diabetes mellitus type 2 . (35%) of the patients give positive family history for goiter.